Kajian Pelaksanaan Kode Etik Aparatur Sipil Negara (ASN) (Studi Kasus Pada Pelaksanaan Kode Etik Aparatur Sipil Negara di Pemerintahan Daerah Kabupaten Ngawi Provinsi Jawa Timur) - dewi, sangrila puspita (JURNAL SOSIAL : Jurnal Penelitian Ilmu-Ilmu Sosial, 2018)
To find out how far the application of code of Civil State Apparatus ethics conducted research with descriptive method using closed instrument and sample (n) 18 people of Local Government with case study in District Ngawi East Java Province, found employee perception to ethics organize good enough but need improvement of work quality through performance contracts, training, competence, rewards and sanctions, and performance evaluations.